Materials selection in mechanical design - Ashby, M. F. (Butterworth-Heinemann, 1999)
Describes a procedure for materials selection in mechanical design, allowing the appropriate materials for a given application to be identified from the full range of materials and section shapes available.
Keywords: Materials.; Engineering design.; elektronické knihy; electronic books